Cluster pairs in the Small Magellanic Cloud. - Hatzidimitriou, D.; Bhatia, R. K. (Astronomy and Astrophysics, 1990)
We have surveyed the cluster system of the SMC with the aim of identifying close pairs of clusters. We find that the number of existing close cluster pairs is significantly (at the 3.5 σ level) larger than the expected number of such pairs due to the chance line-up of single clusters, implying that some of these pairs are physically associated. Comparison with the LMC cluster system shows that the ratio of pairs is similar to the ratio of single clusters in the two galaxies. These results, combined with the earlier results for the LMC, indicate the tendency of clusters to form in pairs, or possibly in groups, at least in the case of irregular galaxies, the probability that the observed number of pairs having formed due to tidal capture being small.
Keywords: Astronomical Catalogs; Astrophysics; Galactic Clusters; Galactic Evolution; Irregular Galaxies; Magellanic Clouds; Sky Surveys (Astronomy); Spatial distribution; star clusters